Portfolio optimization of Shariah and Conventional Assets in FBMKLCI by using mean-variance and mean-lower partial moments / Nor Syazwani Mat Zin, Nurulhuda Zoli and Nik Nur Aqila Mohd - Mat Zin, Nor Syazwani; Zoli, Nurulhuda; Mohd, Nik Nur Aqila (2019)
Nowadays, financial portfolio optimization has a pirntal role for the problem Lhat occun; i11 mathematics, statistics, fiuaucial auJ computatioual literature. In context of Malaysia. the assets are categorized into two which are shariah and conventional assets. Both assets are related to different kinds of business and invrstmrnt artivitirs, hence there wonlcl hr a difference in risks and returns as ,veil. The objective of this study is to identify the risk for portfolio of shariah, conventional and combination of assets (shariah and conventional assets). The closing prices for year 2009 to 2019 are collected from FBMKLCI and FTBSM Hijrah Shariah. The risk in the In-samplr portfolio is minirnized by using Mean-Variance and Mean-LPM with three target returns of 1,1.75 and 2.5 percent. Then, the sample is backtested by using the out of sample to get the realized return. In-sample result shows that the risk of portfolio of combination assets has the lowest risk as compared to shariah snd conventioual while out of samplr analyse the realized return for t hr assets havr a slight diffrent between each other. Then. the optimal Mean-Variance model can also minimize the lower partial nwmeuts. For future research, the researcher might improve this study in other risk measure models snch as the MeanCVaR model. From this model, the researcher could get an accurate result hr.cause it is the risk assessmrnt measure quantifying the amount0 of tail risk the portfolio of investments.